Settlement of Default by the Debtor and Liability of the Creditor in the Pledge Agreement - Dilla Pyarrani; Tiara Puspita Sari; Wina Karlina (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2023)
The condition of people who are experiencing difficulties in the economic field, credit with collateral is needed by community and is the right choice by the community in meeting their needs as an addition to business capital and to meet their daily needs. The purpose of this study to explain the phenomena that occur in debt-receivable agreements with pledged guarantees, the phenomenon that is the existence of customers who are in default. Customers also need to know the responsibilities of a creditor. Research approach with normative juridical analysis. The legal basis for a pawn agreement is regulated by Article 1150 of the Civil Code (Burgelijjk Weetboek). A pawn agreement arises by a legal relationship between debts that are guaranteed to be repaid with movable objects, so that the pawned goods are in the hands of the creditor. Regarding this matter, the creditor must maintain the collateral that was pawn by the debtor. While the debtor is obliged to pay debts to creditors. If one of the parties does not fulfil its obligations, then parties has failed to comply with the agreement. The results from the study show that the legal consequence of debtors who have defaulted are cancellation of agreements and risk transfer. While the responsibility carried out due to the negligence of the creditor on the pawned object is by same item, repair the object and etc in accordance with the negligence that occurred.